Listening after the animals: sound and pastoral care in the zoo. (15th September 2021) - Rice, Tom; Badman‐King, Alexander; Hurn, Samantha; Rose, Paul; Reed, Adam
Abstract: In anthropology and across the humanities and social sciences, zoos have tended to be theorized as places of spectacle. Scholars often focus on the ways in which these institutions enable the viewing of other‐than‐human animals by human publics. This article, however, uses sound‐focused ethnographic fieldwork to engage with two UK zoos and to describe a particular mode of cross‐species listening which is enacted by zookeepers. The concepts of pastoral care and control discussed by Foucault and applied to the zoo context by Braverman are productively reworked and reorientated in order to understand this form of listening. The article also demonstrates the interconnectedness of keeper, visitor, and animal sound worlds, in the process generating an original perspective that complements and enriches conventional zoo studies. Abstrait: Entendre les animaux : son et soins pastoraux au zoo Résumé L'anthropologie, comme les autres sciences humaines et sociales, théorise souvent les zoos comme des lieux de spectacle. Beaucoup de chercheurs s'intéressent à la manière dont ces établissements permettent à des visiteurs humains d'observer des animaux autres qu'humains. Le présent article s'appuie quant à lui sur un travail ethnographique de terrain axé sur le son pour décrire le mode particulier d' écoute interspécifique pratiqué par le personnel de deux zoos du Royaume‐Uni. Les concepts de soin et de pouvoir pastoraux, exposés par Foucault et mis en pratique dans le contexte du zoo par Bravermann, sont revisités de façon productive et réorientés de façon à éclairer cette forme d'écoute. L'article met en évidence les interconnexions entre les univers sonores des soigneurs, des visiteurs et des animaux, créant ainsi un point de vue original qui complète et enrichit les études classiques sur les zoos.